PEMANFAATAN LIMBAH SERBUK GERGAJI UNTUK PRODUKSI BIOETANOL MENGGUNAKAN SEL RAGI IMOBIL SECARA BERULANG - Novianti, Novianti; Mappiratu, Mappiratu; Musafira, Musafira (Natural Science: Journal of Science and Technology, 2013)
Study about the Utilization of sawdust waste as a subtrat in Bioethanol production by using repeated-immobilized yeast cells has been done. The aim of this research was to determine the best ratio of sulfuric acid to sawdust and to determine the optimum hydrolysis time, its in order to get the highest sugars content and alkohol content, and also to know the activity of the immobilized yeast cell for in alkohol production by repeated-use of immobilized cell. It was done by applying  9 levels of sulfuric acid (50%) ratio to sawdust (v/b) {i.e. 2 : 1 (A), 3 : 1 (B), 4 : 1 (C), 5 : 1 (D), 6 : 1 (E), 7 : 1 (F), 8 : 1 (G), 9 : 1 (H) and 10 : 1 (I)}, and 5 levels of hydrolysis time (i.e. 0,5; 1;  1,5;  2; and 2,5) . The result showed that the best ratio of sulfuric acid to sawdust was 5 : 1 (v/b), it could produce the sugars content for about 43,52%. While the best hydrolysis time was 2 hours and it could gave 43,72% of sugars content, when the fermentation proceses was done in 72 hours. The activity of immobilized yeast cell was decreased in repeated-used system, and there was no alcohol can  produced in the fourth time of immobilized yeast cell used.